KAJIAN PERUBAHAN HUKUM DAN PEREKONOMIAN PADA ERA PERDAGANGAN BEBAS DI SEKTOR PERTANIAN - Ariani Ariani (Universitas Borneo Tarakan, 2019)
Abstract National economic development has shown the transformation of the economic structure from agriculture to industry, as well as with the development of the law. Economic indicators showed decline in the share of the agricultural sector as well as an increasing share of the industrial sector in the Gross Domestic Product (GDP) can be bukti.Pertanian in Indonesia is at crossroads jalan.Sebagai supporting the livelihood of millions of Indonesian society, the agricultural sector requires a strong economic growth and rapid .Sektor also need to be one of the main components in the program and the government's strategy to alleviate structural kemiskinan.Transformasi between sectors, it appears that with increasing per capita income, the agricultural sector has decreased the share of the GDP, while the industrial sector on the contrary experienced peningkatan.Kebanyakan developing countries today this has been agreed that the development of industry and agriculture as much as possible to walk semultan. Agriculture provides a market for manufactured goods, feed the urban population, be a source of labor and capital to the industrial sector, as well as generate foreign exchange for the import of machinery and raw materials required by the intermediate industri.Prioritas sector policies to increase food production can be done through the use teknologi.Tipe and direction of technological change is influenced by market forces and pemerintah.Selain research funded research in the country, the source of technological progress is a transfer from outside negeri.Program-local research programs in countries developing in some ways is not replaceable by technology the foreign research results.Keywords: Structural Transformation, GDP, Agricultural Sector, Industrial Secto